Green Economy: Development of Sustainable Dairy Cow Manure Utilization Processes for Farmers in the Northeastern Region of Thailand - Roong Ratikul; Somchai Seviset; Songwut Egwutvongsa (Academic Journal of Interdisciplinary Studies, 2023)
The research aimed to develop and assess the satisfaction of a sustainable utilization process for dairy cow manure for farmers in the Northeast region of Thailand. The population comprised 162 dairy farmers in Pak Chong District, Nakhon Ratchasima Province, Thailand and the group sampling consisted of 150 dairy farmers in Pak Chong District by using a simple random sampling method to analyze the mean and exploratory factor analysis (EFA). Additionally, dairy cow's dung that was used to be processed into organic fertilizer could reduce methane emission by using a newly developed dairy cow's dung converter, which the organic fertilizer yield was qualified as follows: 1) Organic matter = 14.5% by weight, 2) C/N ratio = 11.24:1, 3) electrical conductivity = 4.23 decimals per meter. and 4) the valuable pH = 8.35. Then, the results of the test for the amount of the primary nutrients from the primary macronutrient analysis were total organic carbon = 9.1%, nitrogen = 0.8%, phosphorus = 0.6%, and potassium = 0.84% when using the new converter. Furthermore, it was piloted with a group of farmers in the aforementioned area. From the results, it was found that there were three factors affecting the satisfaction of dairy cow farmers toward the new dairy manure conversion process; namely, the features of the machine, the efficiency of the machine, and the appearance of the machine. Simultaneously, when taking all three factors to evaluate the satisfaction, the following results were found: 1) The features of the machine that is very important (mean = 4.283; SD = 0.661), 2) the efficiency of the machine that is very appropriate (mean = 4.280; SD = 0.528), and 3) the appearance of the machine that is very appropriate (mean = 4.013; SD = 0.632). Then, these three factors were considered as the highlights of the machine for converting dairy cow dung into ready-made organic fertilizer for cultivating plants in organic agriculture that could be seen as being environmentally friendly.

Received: 7 December 2022 / Accepted: 15 February 2023 / Published: 5 March 2023
Keywords: Agriculture Sustainability and Environmental Impact; Agricultural Systems and Practices